Impact of metabolic risk factors on the severity and outcome of patients with alcohol‐associated acute‐on‐chronic liver failure. (29th December 2020) - Duseja, Ajay; De, Arka; Taneja, Sunil; Choudhury, Ashok Kumar; Devarbhavi, Harshad; Hu, Jinhua; Hamid, Saeed S.; Butt, Amna Subhan; Jafri, Syed Muhammad Wasim; Ghazinian, Hasmik; Chawla, Yogesh K.; Dhiman, Radha K.; et al.
Abstract: Background: Metabolic risk factors may impact the severity and outcome of alcoholic liver disease. The present study evaluated this effect in patients with alcohol‐associated acute‐on‐chronic liver failure (ACLF). Methodology: One thousand two hundred and sixteen prospectively enrolled patients with ACLF (males 98%, mean age 42.5 ± 9.4 years, mean CTP, MELD and AARC scores of 12 ± 1.4, 29.7 ± 7 and 9.8 ± 2 respectively) from the Asian Pacific Association for the Study of the Liver (APASL) ACLF Research Consortium (AARC) database were analysed retrospectively. Patients with or without metabolic risk factors were compared for severity (CTP, MELD, AARC scores) and day 30 and 90 mortality. Information on overweight/obesity, type 2 diabetes mellitus (T2DM), hypertension and dyslipidaemia were available in 1028 (85%), 1019 (84%), 1017 (84%) and 965 (79%) patients respectively. Results: Overall, 392 (32%) patients died at day 30 and 528 (43%) at day 90. Overweight/obesity, T2DM, hypertension and dyslipidaemia were present in 154 (15%), 142 (14%), 66 (7%) and 141 (15%) patients, respectively, with no risk factors in 809 (67%) patients. Patients with overweight/obesity had higher MELD scores (30.6 ± 7.1 vs 29.2 ± 6.9, P  = .007) and those with dyslipidaemia had higher AARC scores (10.4 ± 1.2 vs 9.8 ± 2, P  = .014). Overweight/obesity was associated with increased day 30 mortality (HR 1.54, 95% CI 1.06‐2.24, P  = .023). None of other metabolic risk factors, alone or in combination, had any impact on disease severity or mortality. On multivariate analysis, overweight or obesity was significantly associated with 30‐day mortality (aHR 1.91, 95% CI 1.41‐2.59, P  < .001), independent of age, CTP, MELD and AARC scores. Conclusion: Overweight/obesity and dyslipidaemia increase the severity of alcohol‐associated ACLF, and the former also increases the short‐term mortality in these patients.